Liquidity Risk Exposure in Islamic and Conventional Banks - Jaara, Osama Omar; Jaara, Bassam Omar; Shamieh, Jamal; Fendi, Usama Adnan (International Journal of Economics and Financial Issues, 2017)
This research aims to identify the factors influencing the ability of Islamic Banks (IB) and Conventional Banks (CB) to manage liquidity risk; determine the effects of the global financial crisis on Islamic and conventional banks, and propose some mechanisms to improve resilience against liquidity risk. Univariate and panel regression analyses were used. This was made by highlighting the factors affecting Liquidity Risk Exposure (LRE) in relation to a cross-country sample that utilises both accounting and economic data. 204 banks were investigated in the Middle East and North Africa (MENA) region, as well as South-Eastern Asian (SEA) countries during 2005-2012. Results revealed that IB recorded the highest average Liquidity Risk (LR) exposure compared to CB. There are significant differences between IB and CB banks in terms of LR factors. It is found that 92% of LR exposures are instigated by financial crises, banks’ gearing, gross domestic product (GDP), off-balance sheet items, total securities held by the banks, non-earning assets divided by total assets for banks and liquid assets in CB. Keywords: Liquidity Risk, Islamic banks, Risk management. JEL Classification: G32